Prediction of lateral load-displacement curve of concrete-encased steel short columns under shear failure. (1st July 2022) - Xue, Yicong; Shang, Chongxin; Yang, Yong; Yu, Yunlong
Highlights: Composite action in shear-critical concrete-encased steel (CES) members is innovatively defined. Lateral load-displacement curves of CES short columns is proposed based on the behavior decoupling of steel and RC. The proposed curve is validated using existing test results, and the ASCE41-based curve is proven unreliable. The strength redistribution in the proposed curve can well model the post-peak behavior of CES short columns. Abstract: Current design codes (e.g., ASCE/SEI 41-17) fail to predict the lateral load-displacement curves of composite members because the interaction between the structural steel and concrete is complex to consider. Therefore, the seismic assessment and performance-based seismic design of concrete-encased steel (CES) columns are challenging for engineers due to the lack of design guidance, especially for CES short columns failed in brittle shear failure. In this paper, the composite action of CES members under shear is first innovatively explained, namely that the RC and steel parts can be considered as two nonlinear springs in parallel. In this case, the global response can be obtained by gluing the lateral load-displacement relationships of these two parts. Based on this, this paper then proposed a lateral load-displacement curve for CES short columns by gluing the trilinear RC part and the bilinear steel part together, and four turning points characterize the global response: the cracking point associated with the apparent decrease in stiffness as the shear cracks occur; the strength point as the CES short columns fail in shear; the pre-strength point or post-strength point as the peak strength points of the RC and steel parts differ; and the failure point with residual strength. With a detailed calculation procedure, a comparison with experimental results of CES short columns is reported to verify the applicability of the proposed curve. It can be concluded that the proposed curve can produce reasonable predictions of cracking load, cracking displacement, peak load, peak displacement, and strength degradation, while the provisions in ASCE/SEI 41-17 are proven inferior due to the unsuitable curve configurations and rough modeling of shear deformation. Additionally, the explicit stress redistribution process in the proposed curve can explain why CES short columns suffered a milder strength degradation than conventional RC short columns.